[3 + 3] Formal Cycloadditions of Nitrones from Isatins and Azaoxyallyl Cations for Construction of Spirooxindoles. Issue 6 (31st March 2017) - Lin, Weijia; Zhan, Gu; Shi, Minglin; Du, Wei; Chen, Yingchun
Abstract : A [3 + 3] formal cycloaddition reaction between in situ formed azaoxyallyl cations and nitrones from isatins has been developed, furnishing a spectrum of spiro[1, 2, 4‐oxadiazinan‐5‐one]oxindoles in good to excellent yields with excellent diastereoselectivity. This method provides direct and efficient access to potentially bioactive spirooxindoles incorporating a six‐membered heterocyclic scaffold. Abstract : Spirooxindoles incorporating a six‐membered heterocyclic scaffold are efficiently constructed through a [3 + 3] formal cycloaddition reaction between nitrones from isatins and α ‐halohydroxamates under basic conditions.